Penguatan Karakter Nasionalisme dengan Pelestarian Kearifan Lokal Batik Teknik Shibori - Heckie Puspoko Jati, Dionisius; Mediatati, Nani; Listiarum, Febri; Maulinda Sa’diyah, Putri (Citizenship Education, Faculty of Education, Jambi University, 2025)
This study aims to explore the role of batik with the Shibori technique in strengthening nationalistic character through the preservation of local wisdom. Batik, as Indonesia's cultural heritage, carries deep aesthetic and philosophical values, while the Shibori technique, originating from Japan, has been adapted by Indonesian batik artisans to create new works that still uphold traditional values. This research uses a qualitative approach with a descriptive-analytical design, involving interviews, observations, and literature reviews in several well-known batik-producing regions in Indonesia, such as Solo, Yogyakarta, and Pekalongan. The results of the study indicate that the Shibori technique in batik can enrich Indonesian textile art products and strengthen nationalism by fostering pride in local cultural heritage. Furthermore, batik with the Shibori technique also has the potential to introduce batik to younger generations while showcasing Indonesia's cultural richness on the international stage. However, the main challenge is maintaining a balance between preserving traditional techniques and innovating in batik development. The study concludes that Shibori batik plays an essential role in strengthening nationalistic character through the preservation of local wisdom, which can shape the nation's identity and enhance pride in Indonesian culture